2017
DOI: 10.1177/1938965517734941
|View full text |Cite
|
Sign up to set email alerts
|

Couple Roles in Subdecisions on Family Vacations

Abstract: This article studies the roles within couples, the main decision makers in family vacations, for each of the subdecisions into which the purchase process can be divided. This implies not only identifying the role played by each member of the couple in each subdecision but also determining the variables behind whether the man, the woman, or both jointly, have the greatest influence in each case. To this end, the use of 375 sets of questionnaires completed by each partner separately provided greater validity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Nevertheless, other studies support the findings of this study. They hold that when both members of the couple work outside the home, they share out domestic responsibilities for practical reasons, including decisions about holidays, and that they consequently adopt these decisions autonomously (Cosenza and Davis 1980; Rojas-de-Gracia and Alarcón-Urbistondo 2018; Rojas-de-Gracia, Alarcón-Urbistondo, and González-Robles 2018). According to this point of view, if she works out of the home, there is less probability of decisions being made jointly; as a result, the satisfaction experienced will be less than if she did not work outside the home, which is the conclusion reached in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other studies support the findings of this study. They hold that when both members of the couple work outside the home, they share out domestic responsibilities for practical reasons, including decisions about holidays, and that they consequently adopt these decisions autonomously (Cosenza and Davis 1980; Rojas-de-Gracia and Alarcón-Urbistondo 2018; Rojas-de-Gracia, Alarcón-Urbistondo, and González-Robles 2018). According to this point of view, if she works out of the home, there is less probability of decisions being made jointly; as a result, the satisfaction experienced will be less than if she did not work outside the home, which is the conclusion reached in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Family travel decision making is thus a popular topic among tourism academics. Generally, family holiday decision-making studies have focused on three typical decision-making stages: problem recognition, information search behavior and evaluation of alternatives, and final decisions (Decrop 2005; Lederhaus and King 2015; Rojas-de-Gracia and Alarcón-Urbistondo 2018) Other studies have discussed family members’ roles in decision making. For example, Nanda, Hu, and Bai (2007) outlined a conceptual framework of family travel decisions and identified numerous family roles in making decisions, including that of a gatekeeper, information searcher, influencer, decision maker, purchaser, and user.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In studies of families’ vacation decisions, common decision-making types include husband-dominant, wife-dominant, and joint. Recently, an increasing number of studies have revealed that couples engage in holiday decision making jointly through various subdecisions (Rojas-de-Gracia and Alarcón-Urbistondo 2018), during the problem recognition and final decision stages (Rojas-de-Gracia and Alarcón-Urbistondo 2018), or throughout all three stages (Ashraf and Khan 2016; Kancheva and Marinov 2014). Cheng et al.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The data described in this article contain responses about the perceptions of each member of a couple regarding who was the most influential member in various aspects of family vacation decision-making. These aspects refer to the three most frequently studied stages of tourist decision-making: Initiation, information search, and final decision [2], [3], [4], and seven sub-decisions that have received considerable research attention: Destination, accommodation, transport, budget, date, activities, and restaurants [5], [6], [7], [8]. Table 1 shows the variables collected in the data regarding the influence exerted by each member of the couple, as well as their respective categories.…”
Section: Datamentioning
confidence: 99%